Film rating: a comparative analysis in Malaysia and Bangladesh - Islam, Md. Zahidul (Readers Insight Publisher, 2019)
Film rating is a form of censorship where restrictions are imposed on the population on what films a person could view. The main purpose of this paper is to discuss the legal framework of film rating and current film rating process of Malaysia and Bangladesh. This paper also try to indentify the strengths and weaknesses of film rating process of both countries.The researcher mainly adopted qualitative methods. The information has taken from many readings, articles, books, newspapers and statutes. The researcher also conducted interview with the member of the film censorship board, directors and actors of both countries. People in the film industry in both countries accepted the need for film rating as guidance for individuals and parents in choosing film viewing.